2018
DOI: 10.1088/1361-6595/aadb69
|View full text |Cite
|
Sign up to set email alerts
|

Inductively coupled array (INCA) discharge

Abstract: Recently a novel concept for collisionless electron heating and plasma generation at low pressures was proposed theoretically (U Czarnetzki and Kh Tarnev, Phys. Plasmas 21 (2014) 123508). It is based on periodically structured vortex fields which produce certain electron resonances in velocity space. A more detailed investigation of the underlying theory is presented in a companion paper (U Czarnetzki, submitted to Plasma Sources Sci. Technol. (2018), arXiv:1806.00505).Here, the new concept is experimentally r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…Tanskov et al 2015). Obviously, the absolute densities scale linearly with the power coupled to the plasma as expected (Lieberman and Lichtenberg 2005;Ahr et al 2018). The linearity follows from the simple argument that (a) for stationarity, power input and losses must be balanced and (b) all losses are proportional to the electron density.…”
Section: Concept For Integrating the Fokker-planck Heating Operator I...mentioning
confidence: 80%
See 2 more Smart Citations
“…Tanskov et al 2015). Obviously, the absolute densities scale linearly with the power coupled to the plasma as expected (Lieberman and Lichtenberg 2005;Ahr et al 2018). The linearity follows from the simple argument that (a) for stationarity, power input and losses must be balanced and (b) all losses are proportional to the electron density.…”
Section: Concept For Integrating the Fokker-planck Heating Operator I...mentioning
confidence: 80%
“…However, it should be rather straightforward to apply the same general procedure also to other heating scenarios, e.g. in the INCA discharge (Ahr et al 2018) or in ECR discharges (Lieberman and Lichtenberg 2005). The detailed form of the coupling functions will likely be different but the general structure of the heating operator and the structure of the global kinetic model will remain the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed description of the discharge setup can be found elsewhere 9,10 . Here only a brief description is give.…”
Section: Experimental Setup a Discharge Setupmentioning
confidence: 99%
“…The individual coils are connected with each other through copper stripes. The previous studies 9,10 have shown that for a matching to be possible, the coil wiring has to be separated into three parallel branches, each containing 12 coils connected in series.…”
Section: Experimental Setup a Discharge Setupmentioning
confidence: 99%